Pesan Komunikasi Produksi Program Berita Di TVMu - Natasya Amelia Putri; Makroen Sanjaya (STIKes Ibnu Sina Ajibarang, 2024)
Messages are one of the elements in the communication system from the source or communicator to the communicant, which, among other things, can be conveyed through news on television. The effectiveness of delivering communication messages in the form of news via television is largely determined by the message packaging strategy. This research aims to determine the communication messages conveyed through the production process in news on TVMu. This research uses Alex Sobur's message delivery theory. Using the case study method, the research explains how the news packaging process is carried out sequentially according to existing procedures. As a result, it is known that the overall news production process on TVMu has conveyed communication messages starting from the pre-production process, production to post-production.